Analisis Konten Instagram @Cutie.Pas dalam Membangun Brand Awareness Bisnis Thrift: Tinjauan Etika Bisnis Syariah - Wahyu Aliya Nabila; Nurul Huda (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The rapid growth of the thrift business in Indonesia, along with the use of Instagram as a digital marketing platform, underscores the urgency of examining content strategies in building brand awareness and their alignment with ethical values. This study aims to analyze Instagram content of @Cutie.Pas in building brand awareness for the thrift business while reviewing its promotional practices from the perspective of Islamic business ethics. Employing a qualitative approach with netnography method, non-participant online observation was conducted on the @Cutie.Pas Instagram account during October–December 2026, analyzing 416 posts and audience interactions based on brand awareness indicators and Islamic business ethics principles. The findings reveal that @Cutie.Pas content builds brand awareness through three mechanisms: brand recognition through visual consistency, brand association formation through product presentation style, and brand recall reinforcement through audience interaction. From the Islamic business ethics perspective, promotional content demonstrates relative conformity through transparent product information disclosure, inclusion of item conditions to avoid gharar (deception), fair pricing, and responsiveness to audience questions as a manifestation of amanah (trustworthiness). This study concludes that @Cutie.Pas Instagram content not only effectively contributes to building brand awareness but also represents thrift business practices aligned with the principles of honesty (shiddiq), justice ('adl), transparency, and social responsibility within the framework of Islamic business ethics.